Evaluation on the potential of Aquilaria malaccensis for heavy metals phytoremediation in contaminated soil - Abu Bakar Hamzah, Nurul Atikah (2018)
Phytoremediation is one of the methods that can help reduce pollution by absorbing heavy metals through plant roots. A study was conducted at the nursery of Faculty of Forestry UPM to evaluate the potential of Karas (Aquilaria malaccensis) as a phytoremediator species. The objectives of this study were : (i) to determine the effectiveness of A. malaccensis for taking up heavy metals from contaminated soil after harvesting and (ii) to evaluate the potential A. malaccensis as a phytoremediator plant in taking up heavy metals and translocate heavy metal elements in plant parts (leaves, stems, roots) by using an indicator of Translocation Factor (TF) and Bio-concentration Factor (BCF). A. malaccensis saplings were planted in growth media applied with Zn, Cu and Fe. The treatments were T0= control, T1=100ppm of Zn, T2=200ppm of Zn, T3=300ppm of Zn, T4=100ppm of Cu, T5=200ppm of Cu, T6=300ppm of Cu, T7=100ppm of Fe, T8=200ppm of Fe and T9=300ppm of Fe. Each type of treatments was replicated for four times. The highest growth of A. malaccensis was recorded for the T9 growth media. The highest concentration of Zn in the roots of the A. malaccensis plant was in the T3 growth media (14.49mg/kg). The highest accumulation of Fe (350.46 mg/kg) was recorded in the roots of A. malaccensis in the T9 growth media, whereas the stem of the A. malaccensis in T6 recorded the highest Cu accumulation (0.99mg/kg). The Transfer Factor (TF) values were more than 1 but the Bio-concentration Factor (BCF) values were less than 1 for Zn, Cu and Fe. The roots of A. malaccensis were ideal in uptaking and storing Fe, Cu and Zn. More studies need to be conducted, especially in field conditions, to optimize the potential of the A. malaccensis plant as a phytoremediator.